2017
DOI: 10.1111/bjh.14813
|View full text |Cite
|
Sign up to set email alerts
|

Clinical heterogeneity of diffuse large B cell lymphoma following failure of front‐line immunochemotherapy

Abstract: Summary This study aimed to describe the patterns of care and outcomes of diffuse large B cell lymphoma (DLBCL) after failure of front line anthracycline-based immunochemotherapy (IC). Patients with newly diagnosed lymphoma were prospectively enrolled in Molecular Epidemiology Resource (MER) of the University of Iowa/Mayo Clinic Lymphoma Specialized Program of Research Excellence. All DLBCL and primary mediastinal B-cell lymphoma (PMBL) patients treated with front-line anthracycline-based IC were followed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 54 publications
1
48
2
Order By: Relevance
“…Hamadani et al reported that patients with an early relapse had shorter OS than patients with a primary refractory disease who were treated with ASCT (2‐year OS 59% vs 41%). By contrast, 3 recent reports showed that patients with an early relapse had better OS than patients with a primary refractory disease . In our report, these 2 subgroups of refractory patients had comparable outcomes.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…Hamadani et al reported that patients with an early relapse had shorter OS than patients with a primary refractory disease who were treated with ASCT (2‐year OS 59% vs 41%). By contrast, 3 recent reports showed that patients with an early relapse had better OS than patients with a primary refractory disease . In our report, these 2 subgroups of refractory patients had comparable outcomes.…”
Section: Discussioncontrasting
confidence: 70%
“…Therefore, only half of the patients for whom an ASCT is planned present with a chemosensitive disease and ultimately receive an ASCT, yielding a 4‐year overall survival (OS) of 60% to 65% . Furthermore, previous studies have shown that patients with refractory disease have worse outcomes than patients who relapse 1 year after diagnosis . The precise definition of refractoriness can vary between studies, and analyzing the outcomes of patients according to initial chemo‐sensitivity (complete response (CR), partial response (PR), or progression during first‐line treatment) is somewhat controversial .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, patients with primary refractory disease were excluded and approximately two‐thirds of patients in both arms had relapsed ≥1 year after first‐line treatment initiation. Both primary refractory disease and early relapse are associated with poor prognosis (Farooq et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Although standard chemoimmunotherapy is considered curative for more than half of all patients with newly diagnosed diffuse large B-cell lymphoma (DLBCL), an estimated 20% to 30% relapse after an initial remission, and an estimated 10% of patients have primary refractory disease (1,2). High-dose chemotherapy with autologous hematopoietic stem cell transplantation (HSCT) is the usual standard for first relapse of DLBCL, provided that the relapse is chemosensitive, and can cure a subset of patients.…”
Section: Introductionmentioning
confidence: 99%